Relationships among Physical Activity, Pain, and Bone Health in Youth and Adults with Thalassemia: An Observational Study - Ellen B. Fung; Elijah K. Goldberg; Sakina Bambot; Raquel Manzo; Ashutosh Lal (Thalassemia Reports, 2022)
Patients with thalassemia (Thal) engage in less physical activity than non-Thal populations, which may contribute to pain and osteoporosis. The purpose of this study was to assess relationships between physical activity, pain, and low bone mass in a contemporary sample of patients with Thal. Seventy-one patients with Thal (50 adults ≥18 years, 61% male, 82% transfusion-dependent) completed the Brief Pain Inventory Short Form and validated physical activity questionnaires for youth and adults. Nearly half of the patients reported daily somatic pain. Using multiple regression, after controlling for age and gender, sedentary behavior was positively associated with pain severity (p = 0.017, r2 = 0.28). Only 37% of adult participants met CDC recommendations for physical activity. Spine BMD Z-score was higher (−2.1 ± 0.7) in those who met activity guidelines compared to those who did not (−2.8 ± 1.2, p = 0.048). A positive relationship was observed between self-reported physical activity (hours/week) and hip BMD Z-score in adults with Thal after controlling for transfusion status and sedentary activity time (p = 0.009, r2 = 0.25). These results suggest that decreased physical activity and increased sedentary behavior contribute to low bone mass, which may be related to pain severity in some patients with Thal. Studies focused on increasing physical activity may contribute to improved bone health and reduced pain in patients with Thal.